Fiscal burden differentiation between European Union countries as a source of opportunism, moral hazard and unproductive entrepreneurship - Andrzej Pestkowski (Institute of Economic Research (IER), 2016)
Free movement and freedom of establishment existing within the European Union institutions are the main factors which make European Union open for business activities. However, it should be noted that all EU countries have their own tax systems and fiscal policy. This, in turn, differentiates fiscal burden of government imposed onto its taxpayers in each Member State. These differences frequently distort the conditions of establishment. As every entrepreneur is willing to minimize costs, especially when their source are compulsory taxes, mass tax migration between Member States might be expected. Tax avoidance and tax evasion, being a form of tax migration, imply numerous economic, social and legal problems. The aim of this paper is to identify these problems along with their causes and effects in terms of fiscal burden differentiation between Member States. Descriptive, qualitative and quantitative analyses have been applied in order to explain the abovementioned phenomena. Additionally, the analyses have been accompanied by case studies.
Keywords: E26; H26; K34; K42; 330; fiscal burden; tax systems; opportunism; moral hazard; unproductive entrepreneurship